PROBLEMS OF INCREASING THE ACTIVITY OF STUDENTS WITH LOW ASSESSMENT IN DRAWING (World Economics and Finance Bulletin, 2025)
This article describes methodological recommendations on the problems of increasing the activity of students with low drawing skills.
Keywords: knowledge; ability; competence; imagination